CHALLENGES AND OPPORTUNITIES OF DIGITAL INTEGRATION IN MARKETING: A BUSINESS PERSPECTIVE IN EMERGING ECONOMY - Gagauz, Valeri (Economy and Sociology, 2024)
The rapid digitalization of marketing practices has significantly transformed the way businesses engage with their customers, particularly in the B2C segment. However, the adoption and integration of digital marketing strategies remain uneven across different regional and economic contexts. This study focuses on the Republic of Moldova, an emerging market where businesses face unique challenges and opportunities in implementing digital marketing tools. The research aims to explore how local companies navigate the complexities of digital transformation while addressing market-specific factors such as consumer behavior, resource limitations, and infrastructural barriers.Using a case study approach, in-depth interviews were conducted with representatives from five companies of varying sizes operating in the B2C sector. The research examines the extent to which these businesses utilize digital tools, including customer relationship management (CRM) systems, social media platforms, and branding strategies, to attract and retain customers. Special attention is given to the integration of online and offline channels, the role of end-to-end analytics in optimizing marketing effectiveness, and the challenges associated with implementing these technologies in a resource-constrained environment.The study also investigates the strategic decisions companies make regarding digital investments and the trade-offs between automation, customer engagement, and operational efficiency. By providing insights into the digital marketing practices of Moldovan companies, this research contributes to a better understanding of digital transformation in emerging markets. The findings are particularly relevant for business practitioners and policymakers seeking to enhance digital competitiveness in similar contexts, offering practical recommendations for overcoming barriers and maximizing the benefits of digital marketing integration.